Formulation of natural non-toxic mouthwash lotion from extraction of jathropa curcas latex - Siti Zuhaila, Zulkepeli (2012)
Latex from the Jatropha curcas(Euphorbiaceae)has been used traditionally in the medical region.It is can be used to cure many illness including the illness that related to tooth and anti-microbial activity.The objective of this research is to formulate the non-toxics mouthwash lotion from the extraction of Jatropha curcas latex. This formulation is regarding of uses of Jatropha Latex as the raw material,As for the method of analysis,In Vitro method will be used in order to test and observe the antimicrobial activities.Meanwhile to check the stability of this mouthwash,the stability test will be done.To formulate the mouthwash,various weight of Jatropha curcas latex will be added in the formulation.This mouthwash is also expected to work for the antimicrobial action and prevent bad breath. Jatropha curcas latex has very high potential in order to improve the formulation of the mouthwash and other dental health product.